PENGARUH OPINI AUDIT TAHUN SEBELUMNYA, PROFITABILITAS, AUDIT TENURE, DAN SISTEM PENGENDALIAN MUTU TERHADAP OPINI AUDIT GOING CONCERN - Aji Purnama Ramadhan, - (2021)
This research was conducted to examine the effect of previous year's audit opinion, profitability, audit tenure, and quality control systems on going concern audit opinion. This study uses mining sector companies and Public Accounting Firms (KAP) that audited mining sector companies as samples in the study. The data analysis technique used is Path Analysis or path analysis software SmartPLS 3 with a significance level of 5%. The results in this study obtained (1) previous year's audit opinion has a significant effect on going concern audit opinion (2) profitability has a significant effect on going concern audit opinion (3) audit tenure has no effect on going concern audit opinion (4) the quality control system has no effect on going concern audit opinion (5) previous year's audit opinion has no effect on going concern audit opinion through the quality control system (6) profitability does not affect going concern audit opinion through the quality control system (7) audit tenure has no effect on going concern audit opinion through the quality control system.